2009
DOI: 10.1016/j.jvs.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease and methylenetetrahydrofolate reductase (MTHFR) C677T mutations: A case-control study and meta-analysis

Abstract: We have found a strong association between raised homocysteine, the TT genotype, and PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
0
50
0
5
Order By: Relevance
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…The homozygous and heterozygous genotypes (CT) and (TT) have been shown to be associated with raised Hcy levels and lower MTHFR enzyme concentrations. In one study there was a 36% difference in mean Hcy levels between wildtype and TT genotypes (Khandanpour et al, 2009), while a 47% difference was demonstrated in another study (Rassoul et al, 2000). Further to this, a strong association has been demonstrated between the TT genotype, hyperHcy and coronary, cerebro and peripheral atherosclerotic disease (Khandanpour et al, 2009;Klerk et al, 2002;Moat et al, 2004).…”
Section: Mthfr Genementioning
confidence: 94%
“…In one study there was a 36% difference in mean Hcy levels between wildtype and TT genotypes (Khandanpour et al, 2009), while a 47% difference was demonstrated in another study (Rassoul et al, 2000). Further to this, a strong association has been demonstrated between the TT genotype, hyperHcy and coronary, cerebro and peripheral atherosclerotic disease (Khandanpour et al, 2009;Klerk et al, 2002;Moat et al, 2004). Significantly, the association of the MTHFR genotype with Hcy levels is only observed when concomitant inadequate folate concentrations are present (Guilliams, 2004;Castro et al, 2006), although low folate levels independent of MTHFR have not been shown to cause hyperHcy (Spark et al, 2003).…”
Section: Mthfr Genementioning
confidence: 94%
See 1 more Smart Citation
“…Kafkas ırkında homozigot MTHFR C677T mutasyonunun sıklığı %5-% 20 arasında değişmektedir (25). Dokuz ayrı çalışmayı kapsayan bir meta-analizde MTHFR C677T alelinin artmış PAH riskiyle ilişkili olduğu gösterilmiştir (26). Aksine, başka bir çalışmada MTHFR C677T polimorfizminin PAH için bir risk faktörü olmadığı bildirilmiştir (11).…”
unclassified